Liberal blood transfusion strategies and associated infection in orthopedic patients: A meta-analysis. Issue 10 (12th March 2021) - Wang, Ying; Chen, Junli; Yang, Zhitang; Liu, Yugang
Abstract: Objective: It remains unclear whether transfusion strategies during orthopedic surgery and infection are related. The purpose of this study is to evaluate whether liberal blood transfusion strategies contribute to infection risk in orthopedic patients by analyzing randomized controlled trials (RCTs). Methods: RCTs with liberal versus restrictive red blood cell (RBC) transfusion strategies were identified by searching PubMed, Embase, the Cochrane Central Register of Controlled Trials from their inception to July 2019. Ten studies with infections as outcomes were included in the final analysis. According to the Jadad scale, all studies were considered to be of high quality. Results: Ten trials involving 3938 participants were included in this study. The pooled risk ratio (RR) for the association between liberal transfusion strategy and infection was 1.34 (95% confidence intervals [CI], 0.94–1.90; P = .106). The sensitivity analysis indicated unstable results, and no significant publication bias was observed. Conclusion: This pooled analysis of RCTs demonstrates that liberal transfusion strategies in orthopedic patients result in a nonsignificant increase in infections compared with more restrictive strategies. The conclusions are mainly based on retrospective studies and should not be considered as recommendation before they are supported by larger scale and well-designed RCTs. Abstract : Supplemental Digital Content is available in the text